Colorectal cancer stage at diagnosis in migrants and non-migrants: a cross-sectional analysis of the KoMigra Study in Germany - Dahlhaus, Anne; Siebenhofer, Andrea; Guethlin, Corina; Taubenroth, Maja; Albay, Zeycan; Schulz-Rothe, Sylvia; Singer, Susanne; Plath, Jasper (Zeitschrift für Gastroenterologie, 2018)
Background Colorectal cancer is one leading cause of cancer-related morbidity and mortality. Its prognosis depends largely on tumour stage at diagnosis. Migration status was associated with late stage at diagnosis in some studies, yet results are inconsistent.Methods The cross-sectional study “The Diagnostics of Colorectal Carcinoma in Migrants and Non-Migrants in Germany” (KoMigra) investigated the association between migration background and tumour stage of colorectal cancer at diagnosis in a large German urban area. Patient variables were collected via a survey translated into nine languages. Data on tumour stage were extracted from medical records.Results 437 patients could be recruited for analysis. Explorative logistic regression yielded no significant difference for tumour stage “I” versus “II-IV” according to the tumour classification “Union Internationale Contre le Cancer” (UICC) between migrants and non-migrants. Although the odds of a higher tumour stage were consistently higher in migrants than non-migrants, the effect estimates had wide confidence intervals. In descriptive analyses, migrants reported symptoms more often and for longer time than non-migrants. This was especially true for patients with poor proficiency of German.Conclusions Migration background was not significantly associated with advanced tumour stage at diagnosis. However, the effect of poor language proficiency should be explored further.
Keywords: Colorectal cancer; cross-sectional analysis; migrants; UICC tumor stage